Dementia in older people: an update. Issue 11 (November 2014) - LoGiudice, D.; Watson, R.
Abstract: Dementia is a common condition of the elderly characterised by multiple cognitive deficits resulting in a decline from previous level of function. In the older person, multiple pathologies contribute, including changes commonly seen in Alzheimer disease, dementia with Lewy bodies in addition to vascular changes. Comorbid factors, such as depression, delirium and polypharmacy can contribute to cognitive decline. Novel biomarkers and neuroimaging techniques may assist in the near future to improve accuracy of diagnosis. To date, pharmacological therapies have been largely unsuccessful and provide symptomatic relief only. The timely diagnosis of dementia can facilitate important discussions regarding personal and financial planning and introduce education and supports to the person with dementia and their carers. The person with dementia commonly experiences behavioural and psychological symptoms of dementia that may cause much distress, including to families and carers. Clinical guidelines indicate non‐pharmacological approaches as first line measures, including attention to pain, nutrition and the environment. Dementia is recognised as a National Health Priority in Australia, and efforts to target risk factors as preventative measures to delay onset of dementia require further urgent consideration.